Chemical Composition and Antimicrobial Activities of the Essential Oil from the Flowers of Delphinium formosum - GULEC, CANAN; YAYLI, NURAN; YESILGIL, PINAR; TERZIOGLU, SALIH; YAYLI, NURETTIN (Asian Journal of Chemistry, 2010)
The essential oil from the flowers of Delphinium formosum Boiss. et Huet. (Ranunculaceae) was obtained by hydrodistillation in a Clevenger-type apparatus and analyzed by GC-MS. 68 Components were identified in the oil. The main components in the essential oil from the flowers of D. formosum were found to be tricosane (30.9 %), heneicosane (8.2 %), pentacosane (6.6 %), linalool (2.3 %) docosane (2.2 %) and phytol (2.1 %). The antimicrobial activity of the isolated essential oil from the flowers of the plant was also investigated and it showed moderate antibacterial activity against only E. faecalis and S. aureus. No antibacterial activity against other 5 bacteria and antifungal activity against 2 yeast-like fungi were observed.